Meteorologie und Geomagnetik als Auslöser der internationalen Polarforschung: Amerkungen zur Ideengeschichte der Polarjahre - Krause, Reinhard A. (2008)
The article focuses on meteorology and geomagnetics and their growing significance in the nineteenth century, and discusses the substantial impact of these complex sciences on the economy. In both cases it became obvious that data from higher latitudes was essential for further progress in the respective discipline - a circumstance which served as a strong catalyst for the realization of polar expeditions. However, what was needed was isochronal data of the kind that could only be obtained with a sufficient number of circumpolar observation sites located - to the extent possible - at equal distances from one another. This task exceeded the capacities of individual countries; international cooperation became a must, and the first International Polar Year was carried out in 1882/83. In the course of the International Polar Years I, II (1932/33) and III (International Geophysical Year 1957/58), the focus of scientific interest broadened to include ever higher layers of the atmosphere. The first satellites were employed, and the threshold to outer space thus crossed. The fourth Polar Year (2007-09) did not follow this trend. Instead, it concentrated strongly on researching the changes in the biosphere brought about by man. The article is interspersed with reflections on the interrelationship between politics and science which played a major role in the development of the exemplary Antarctic Treaty Systems. begutachtet (peer reviewed) Veröffentlichungsversion peer reviewed Published Version